The ROLE OF LOCUS OF CONTROL TOWARD WORK-STUDY CONFLICT ON TRIDINANTI UNIVERSITY STUDENTS WHO WORK - Rifda Alda Ufaira; Pratiwi, Marisya (Psychology Journal of Mental Health, 2019)
The research objective was to determine the role of locus of control toward work-study conflict on Tridinanti University students who work. The major hypothesis, has a role of locus of control toward work-study conflict. The minor hypothesis, has a role internal locus of control toward work-study conflict, and has a role of external locus of control toward work-study conflict. The sample was the Tridinanti University students who work from in the armed forces of 2015, 2016 and 2017 who have time to work at least 20 hours every week as many as 148 people. The scale used is the scale of locus of control from Rotter (1990) and scale of work-study conflict from Markel and Frone (1998). Data analysis is using multiple regression. The result of major hypothesis showed that has a role of locus of control toward work-study conflict with R square = 0,105 and p = 0,000. The result minor hypothesis showed that has a role of internal locus of control toward work-study conflict with p = 0,002 and has a role of external locus of control toward work-study conflict with p = 0,000.